Optical and non‐optical methods for detection and characterization of microparticles and exosomes - VAN DER POL, E.; HOEKSTRA, A. G.; STURK, A.; OTTO, C.; VAN LEEUWEN, T. G.; NIEUWLAND, R. (Journal of thrombosis and haemostasis, 2010)
Microparticles and exosomes are cell‐derived microvesicles present in body fluids that play a role in coagulation, inflammation, cellular homeostasis and survival, intercellular communication, and transport. Despite increasing scientific and clinical interest, no standard procedures are available for the isolation, detection and characterization of microparticles and exosomes, because their size is below the reach of conventional detection methods. Our objective is to give an overview of currently available and potentially applicable methods for optical and non‐optical determination of the size, concentration, morphology, biochemical composition and cellular origin of microparticles and exosomes. The working principle of all methods is briefly discussed, as well as their applications and limitations based on the underlying physical parameters of the technique. For most methods, the expected size distribution for a given microvesicle population is determined. The explanations of the physical background and the outcomes of our calculations provide insights into the capabilities of each method and make a comparison possible between the discussed methods. In conclusion, several (combinations of) methods can detect clinically relevant properties of microparticles and exosomes. These methods should be further explored and validated by comparing measurement results so that accurate, reliable and fast solutions come within reach.